Design and Simulation of a Damper with Negative Stiffness for Vibration Mitigation from Drilling Equipment to a Semi-Submersible Platform. (10th July 2020) - Zhang, Yuan; Wang, Shuqing; Fang, Hui; Han, Huawei; Xu, Yihua
Abstract : A negative-stiffness damper (NSD) that incorporates eccentric columns and high-stiffness springs is proposed for vibration mitigation from drilling equipment to a semi-submersible platform. Eccentric columns are considered as negative-stiffness elements, which can provide high static stiffness and achieve negative stiffness with hysteresis energy dissipation caused by buckling mode transition under dynamic conditions. With the assistance of high-stiffness springs, the damper possesses a hysteresis loop that can dissipate vibration energy and mitigate responses. Firstly, the hysteresis characteristics and negative stiffness of eccentric columns are analyzed. Then, the design principle of the NSD is derived, and several characteristics required for applications are investigated. In addition, an NSD system is designed for a target drilling mud pump based on measured data, and the mitigation performance is analyzed by comparing the vibration responses between cases of the proposed NSD system and the steel pedestal. The results demonstrate that the proposed system can effectively reduce the width of affected coverage and the magnitudes of vibration responses. The investigations performed in this paper not only provide the design principle of the new damper, but also prove the great potential of the proposed damper in vibration mitigation from drilling equipment to the hull of the platform.